Dermatophytosis: clinical profile and association between socio-demographic factors and duration of infection - R., Mahalakshmi; R., Apoorva; Joshua, Jefferson (International Journal of Research in Dermatology, 2017)
Background: Dermatophytes are fungi that break down keratin of the stratum corneum and grow. They cause superficial infections of the skin, hair, and nail that are referred to as tinea infections. This study aims to assess the socio-demographic factors and clinical profile of subjects with dermatophytic infections and their impact on the duration of the illness. Methods: 200 random subjects with dermatophytic infections were enrolled and assessed clinically. Results: There was significant association between duration of infection with age, diabetes, living condition and personal factors. Conclusions: The impact of age, diabetes, living condition and personal factors on susceptibility to and duration of dermatophytic infections was elucidated.